SQUAMOUS CELL CARCINOMA OF THE CONJUNCTIVA: ANALYSIS OF FIFTEEN CASES - Baig, Mirza Shafiq Ali; Dareshani, Shehla; Ali, Mir Amjad; Khan, Mohammad Shafique (Journal of Ayub Medical College Abbottabad, 2009)
Background: To document various clinical presentations and management options of conjunctival squamous cell carcinoma (CSCC) in patients attending ophthalmic out patients department (OPD) of a tertiary care centre. This case series was carried out in the Department of Ophthalmology Civil Hospital and, Dow University of Health Sciences, Karachi and were reviewed from June 2004 to December 2007. Methods: Socio-demographic data and clinical features of patients with biopsy proven conjunctival squamous cell carcinoma were recorded and analysed. All patients underwent complete ophthalmic examination by a fellow ophthalmologist and clinical findings were recorded on a prescribed Performa. Data was analysed in terms of frequency, means and median by SPSS for windows V.15. Results: Seventy-two percent of the patients were male and 28% were female, more than 80% of patients were in the age group of seventy years and above. Eighteen percent of patients developed intraocular invasion and the eyes had to be enucleated. Conclusion: CSCC occurs in sun damaged ocular surface usually at limbus, elderly men are more commonly involve, recurrence is a feature of disease and high risk in older individual. In our treatment we used various therapies, excision with clear margin, topical mitomycin C adjunctive cryotherapy and amniotic graft. Keywords: Conjunctival squamous cell carcinoma, elderly men, clinical presentations, recurrence, management options